Edukasi Empat Pilar Untuk Menurunkan Gula Darah Pasien Diabetes Melitus Type II - Ririn Julianisme Nainggolan; Muhammad Erdianta Samosir; Logis Mawarni Tambunan; Eva Latifah Nurhayati; Rafael Ginting; Lisnawati Lubis (JINTAN: Jurnal Ilmu Keperawatan, 2023)
The Emergency Department is one of the most important units of a hospital that functions as a place to handle emergencies at the main gate. IGD crowding is defined as the main condition in emergency services that can exceed the ability, IGD services are the type of quality care in a timely manner. Triage is a type of assessment that is precise, fast, and responsive with the time possible in utilizing human resources, facilities, and equipment efficiently which aims to classify and select all types of patients who need help and prioritize their actions. In the Emergency Department length of stay and Waiting time can see clinical performance and density levels. length of stay in the Emergency Department can see clinical workload and overcrowding levels. This study used a correlation analytic research procedure using a cross-sectional approach which aims to determine the relationship between waiting for time and Length of Stay and patient satisfaction in the Emergency Department of RSU. Royal Prima Marelan. 72 respondents were studied, and 52 respondents (72.3) were satisfied with the waiting time and Length of Stay of the Emergency Room of the Royal Prima Marelan Hospital. From the Chi-Square statistical test, the value obtained is p-value = 0.00 (p <0.05) so that the Alternative Hypothesis (Ha) can be accepted, which means that there is no relationship between waiting time and Length Of Stay and satisfaction of IGD.